Safety before Comfort: A Focused Enquiry of Nepal Skilled Birth Attendants’ Concepts of Respectful Maternity Care - Erlandsson, K; Tamrakar Sayami, J; Sapkota, S (2016)
Background: Respectful maternity care is the universal right of childbearing women, but in Nepal there are no midwives to deliver this care and it is provided by skilled birth attendants (SBAs), who may be physicians, certified nurses, auxiliary nurse-midwives or degree-trained nurses. The aim of this study was to explore how this concept of respectful maternity care was perceived by SBAs in practice. Methods: Focus group discussions were used and the setting was two tertiary level maternity hospitals in Nepal. Ethical approval for the study was obtained from the Nepal Health Research Council. A total of 24 SBAs were recruited voluntarily from the maternity units. Data were analyzed using a phenomenographic approach and interpretation was verified by the focus group facilitator and note-taker. Results: Five categories, divided into16 sub-categories, present the SBAs’ collective description of respectful care. Conclusions: SBAs understood that respectful care at birth was important, but argued that ‘safety comes before comfort’. To achieve safe maternity care, the contribution of relatives is essential, in addition to the provision of medical care. Keywords: evidence-based midwifery; focus group discussions; maternity care; midwifery; phenomenographic analysis.